The impact of human resource management (hrm) practices on employee satisfaction level and performance - Swaroopa Dubisetty; K Sreenivasulu Reddy (Journal of Management and Science, 2022)
Human Resource Management is a significant function in a company designed to improve human resource performance in provision of their management strategic objectives. Human resource is primarily concerned with how workforces are maintained with in companies' concentrating on plans, procedures and systems. This study focuses on Information Technology sector in India.This study analyzes the Human Resource Management (HRM) practices that increase employee satisfaction towards the company to enhance employee performance in the organization. Effective Human Resource practices can reduce employee turnover and increase retention rate within an organization. These practices are health and safety measures, Working environment, Welfare programmes, Training and Development, Compensation management, Reward management, Industrial relations, Work life balance, and Fringe benefits. The analysis identified the significance of employee retention practices to improve retention rate of IT organizations. The study targeted a sample of 615 respondents. A questionnaire was developed in this analysis with the help of previous studies or literature to measure the identified HR practices and related with employee retention. Samples were collected using questionnaire from 102 employees in order to test the hypothesis. ANOVA test was done using SPSS_v20 to find out the impact of Human resource practices variables on employee satisfaction level and performance. It was found that there was a significant relationship and identified major impact of reward management and compensation plans on employee performance whereas welfare programmes had less impact on employee performance.